Tool Design for Assembly and Disassembly of Mold for Injection Molding Maintenance and Service - Supiyanto, Muhammad NurFaiz; Hehsan, Haffidzudin (Progress in Engineering Application and Technology, 2025)
The maintenance of injection molding dies is a critical process in ensuring the longevity and efficiency of the molding process. However, the current methods of assembling and disassembling molds, particularly in the maintenance department, pose significant challenges, including safety risks and inefficiencies. This study aims to design and analyze a specialized tool for the assembly and disassembly of injection molding dies, focusing on improving safety and efficiency. The tool is designed using SolidWorks software, and its structural integrity is evaluated using Finite Element Analysis (FEA). Three designs were conceptualized, inspired by hydraulic lifters and hydraulic engine cranes. The results indicate that Design 1, with stress levels ranging from 28.76 MPa to 38.36 MPa under varying loads, is the most stable and reliable, while Design 2 is unsuitable due to its high stress levels and deformation. Design 3 offers a balance between flexibility and rigidity, making it suitable for specific applications. The study concludes that the developed tool can significantly enhance mold maintenance practices, ensuring safety and efficiency in the workplace.